2022
DOI: 10.3390/ijerph192417091
|View full text |Cite
|
Sign up to set email alerts
|

Status and Prospect of Ecological Environment in the Belt and Road Initiative Regions

Abstract: With the widespread recognition and in-depth implementation of the Belt and Road Initiative (BRI), especially in the context of global climate change, the ecological environment of Belt and Road Initiative regions might be confronted with pressures and challenges with rapid socioeconomic development. In response to those potential environmental challenges, China has put forward Green BRI and enriched the new Silk Road with more environmental connotations, aiming to reduce the conflict between economic developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 93 publications
0
1
0
Order By: Relevance
“…Li et al [36] found an increase in grassland area (i.e., 3.78 × 10 3 km 2 ) and a decrease in desertified land area (i.e., 3.17 × 10 3 km 2 ) from 1980 to 2020. Furthermore, under the influence of climate change, land use changes such as glacier retreat [37] and expansion of lake areas [38,39] in the HXR have become more complex. These changes are expected to have an impact on ESV.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al [36] found an increase in grassland area (i.e., 3.78 × 10 3 km 2 ) and a decrease in desertified land area (i.e., 3.17 × 10 3 km 2 ) from 1980 to 2020. Furthermore, under the influence of climate change, land use changes such as glacier retreat [37] and expansion of lake areas [38,39] in the HXR have become more complex. These changes are expected to have an impact on ESV.…”
Section: Introductionmentioning
confidence: 99%